1 and 5 year survival estimates for people with cirrhosis of the liver in England, 1998–2009: a large population study - Ratib, Sonia; Fleming, Kate M.; Crooks, Colin J.; Aithal, Guru P.; West, Joe (Elsevier, 2014)
BACKGROUND & AIMS: Large, population-based studies that have included the full spectrum of cirrhosis estimating survival, taking into account time-at-risk are lacking. We aimed to report 1- and 5-year average survival rates for people with cirrhosis to be used in a clinical and healthcare policy setting.